Effect of temperature on the thermodynamic and spectroscopic properties of Np(v) complexes with picolinate1. Issue 92 (8th October 2015) - Zhang, Zhicheng; Yang, Yanqiu; Liu, Guokui; Luo, Shunzhong; Rao, Linfeng
<x xml:space="preserve">Abstract</x> The effect of temperature on the thermodynamic and spectroscopic properties of Np(v) complexes with picolinate was investigated.